Immunization against COVID-19: A Comprehensive Review on the Leading Vaccines - Srinivasan, Ananyaa; Rajesh, Vijaishree; Thamilvanan, Dharani; Ganesh, Sanjeev K.; Chandrasekaran, Subathra Devi. (Coronaviruses, 2024)
The global impact of coronavirus disease (COVID-19) has prompted researchers and scientists to develop effective vaccines to contain the spread of the pandemic. This has led to the deployment of a range of vaccines from different pharmaceutical companies across the globe in a very short span of time. The current article provides a comprehensive record of all the vaccines developed against coronavirus with a specific focus on the mode of action and administration of the vaccines. The article also dwells on the composition, possible side effects and criteria for the choice of individuals for the administration of the vaccines. Vaccines against COVID-19 have been broadly categorized as mRNA vaccines, adenoviral vector-based vaccines and inactivated vaccines. Among the mRNA vaccines, the Pfizer vaccine and Moderna vaccines gained significant popularity. The Oxford Astro Zeneca vaccine and Sputnik V were the most effective viral vector vaccines. Inactivated vaccines such as Covaxin and Sinovac were also significant contributions to contain the pandemic. The review discusses the efficiency of vaccines against the variants of SARS-CoV-2. The review will provide a clear-cut idea about all kinds of exciting vaccines against COVID-19. At present, where the immediate crisis of the pandemic has been successfully contained, this article acts as a resource for future public health endeavors, policy makers, health care professionals and the general public to understand the diversity of COVID-19 vaccines.
Keywords: COVID-19